The effect of direct democracy on the level and structure of local taxes - Asatryan, Zareh; Baskaran, Thushyanthan; Heinemann, Friedrich (Regional science and urban economics, 2017)
We study the effect of direct democracy on local taxation. Our setting is the German federal state of Bavaria, where in 1995 a state-wide reform introduced the possibility to initiate direct democratic legislation into the local government code. Relying on a sample of all Bavarian municipalities over 1980-2011, we hypothesize that complementing a representative form of government with the initiative process leads to (i) higher local tax rates and (ii) a shift of the local tax mix from taxes with broader (property taxes) to taxes with narrower bases (business taxes). For identification, we rely on a difference-in-discontinuity design. Our results suggest that the ease with which local initiatives can be implemented - measured by signature and quorum requirements - increases local tax rates and shift the tax mix toward taxes with narrower bases.